Best Friends - Book 2 - Hale, Shannon; Pham, LeUyen; Sycamore, Hilary (New York : First Second, 2019)
When she becomes part of the in-crowd, Shannon begins to question whether she wants to remain there, in this autobiographical graphic novel about popularity, first boyfriends, and finding a path in life.
Keywords: Hale, Shannon -- Childhood and youth; Comic books, strips, etc; Hale, Shannon -- Childhood and youth; Cartoons and comics; Best friends -- Comic books, strips, etc; Friendship in children -- Comic books, strips, etc; Popularity -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Best friends -- Cartoons and comics; Friendship -- Cartoons and comics; Popularity -- Cartoons and comics; Schools -- Cartoons and comics; Best friends -- Cartoons and comics; Friendship -- Cartoons and comics; Popularity -- Cartoons and comics; Schools -- Cartoons and comics; Best friends -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Comics (Graphic works); Autobiographical comics; Autobiographies